2019
DOI: 10.1111/desc.12820
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity and gross motor skills with executive function in preschool children from low‐income South African settings

Abstract: Executive function is foundational for cognitive development. Previous research has shown both gross motor skills and physical activity to be related to executive function. However, evidence for these relationships in the preschool years, as well as in low‐ and middle‐income countries is lacking. Therefore, this study aimed to investigate the relationships between components of executive function (inhibition, shifting and working memory) and gross motor skills (locomotor skills and object control skills) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
137
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 69 publications
17
137
4
6
Order By: Relevance
“…Pre-school gross motor abilities were also significantly, albeit modestly, associated with children's self-regulation growth. This is consistent with suggestions of common mechanisms (i.e., executive functions) that are implicated in both self-regulation and motor learning (36)(37)(38), such that both show common areas of neural activation, are impaired after damage to neural regions for the other, and are often both impaired in cognitive disorders, such as ADHD and dyslexia. Indeed, tasks that are motor-demanding for young children, such as navigating uneven surfaces and/or obstacles, are more cognitively demanding and lead to more cognitive errors than less cognitively demanding motor tasks (39).…”
Section: Resultssupporting
confidence: 90%
“…Pre-school gross motor abilities were also significantly, albeit modestly, associated with children's self-regulation growth. This is consistent with suggestions of common mechanisms (i.e., executive functions) that are implicated in both self-regulation and motor learning (36)(37)(38), such that both show common areas of neural activation, are impaired after damage to neural regions for the other, and are often both impaired in cognitive disorders, such as ADHD and dyslexia. Indeed, tasks that are motor-demanding for young children, such as navigating uneven surfaces and/or obstacles, are more cognitively demanding and lead to more cognitive errors than less cognitively demanding motor tasks (39).…”
Section: Resultssupporting
confidence: 90%
“…22 Gross motor skills were found to be good amongst 0-5 year old children in SA. [23][24][25][26][27] In the study with preschool-aged children from a low-income, rural setting, better gross motor skills (as measured by the Test of Gross Motor Development-Version 2, TGMD-2 28 ) were associated with objectively measured MVPA and vigorous-intensity physical activity. This study also found that directly observed MVPA during preschool time was positively associated with gross motor skills.…”
Section: Physical Activitymentioning
confidence: 99%
“…For example, we do not know how young children’s exposure to multilingualism in low‐ and middle‐income countries relates to EFs, despite the reported benefits of bilingualism for EFs in high‐income countries (Thomas‐Sunesson, Hakuta, & Bialystok, ). In addition, young children in many low‐ and middle‐income countries walk long distances to school, but it remains unclear whether this extensive physical activity can be leveraged to promote, rather than hinder, EFs by making it more cognitively challenging (Cook et al, ; Diamond & Ling, ). Furthermore, young children in low‐ and middle‐income countries spend considerable time in informal activities with peers, such as running, clapping, rhyming, and playing ball games.…”
Section: Contextual Influences On Executive Function Skillsmentioning
confidence: 99%